Intersectoral action: local governments promoting health - Rantala, Riikka; Bortz, Martin; Armada, Francisco (Health promotion international, 2014)
Abstract. Many local governments around the world promote health through intersectoral action, but to date there has been little systematic evidence of these e
Gesehen am 13.08.2020